Review of Evaluation: The International Journal of Theory, Research, and Practice, Volumes 11(2), 11(3), and 11(4) - Daniela C. Schröter (The Evaluation Center at Western Michigan University, 2006)
The following contribution provides a summary of Volumes 11(2), 11(3), and 11(4) of Evaluation: The International Journal of Theory, Research and Practice (2005). The central motif of issue 11(2) is learning, that is, learning from theories of change, "accountability (f)or learning," learning aided by cluster evaluation, facets of organizational learning, and learning from the use of certain research designs. Issue 11(3) centers on issues and approaches of (primarily policy) evaluation in different countries (Belgium, the United Kingdom, Norway, and Japan) and contexts (development evaluation, educational evaluation, social service evaluation). Issue 11(4) stresses evaluation designs, methodological approaches, evaluator competencies, and problems of bottom-up versus top-down evaluation. The following briefly summarized the contributions of each volume.